Developing novice researchers understandings of research - Clear, Tony; Young, A. (NACCQ, 2001)
This paper reports progress from an action research programme to develop an active research community amongst New Zealand computing educators. Since 1998 the National Advisory Committee on Computing Qualifications (NACCQ) has sponsored a number of "Getting Started in Research Workshops". Topics addressed in the workshops have included definitions of research, the maturity profiles of researchers and the nature of research conducted under different research paradigms. The workshops have developed from an initial educative and developmental focus for novice researchers, to one that now embodies more of a critical perspective, in which participants reflect upon and collectively discuss their own beliefs and understandings as educators and researchers within the NACCQ sector. This has required the development of specific self-assessment instruments. These include an instrument for assessing researcher maturity and a further instrument for self-assessment of paradigm preferences in curriculum development and research. Preliminary results from these self-assessments have been reported (Clear & Young, 2001) which give some insights into the understandings about research of computing educators and novice researchers in the sector. But developing and refining these self-assessment instruments is a continuing process. Since this self-assessment process has been undertaken as a means of actively modelling use of the critical method in research, determining forms of analysis that are consonant with this paradigm is a current issue for the authors. This paper will discuss the context, the instruments developed, review the issues related to analysis of data gathered to date, and indicate future directions for this research.